2020
DOI: 10.1101/2020.05.08.20095968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of underlying morbidities on the occurrence of deaths in COVID-19 patients: A systematic review and meta-analysis

Abstract: Background: Coronavirus disease 2019 , the most hectic pandemic of the era, is increasing exponentially and taking thousands of lives worldwide. This study aimed to assess the prevalence of pre-existing morbidities among COVID-19 infected patients and their mortality risks against each type of pre-existing morbidity category. Methods:To conduct this systematic review and meta-analysis, Medline, Web of Science, Scopus, and CINAHL databases were searched using specified relavent keywords. Further searches were c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 80 publications
6
23
0
2
Order By: Relevance
“…health conditions, such as obesity, cancer, type 2 diabetes, and renal conditions, were prevalent among patients with worse COVID-19 outcomes. 34,45,46,55 Notably, our findings largely agree with recent published work examining racial/ethnic differences in COVID-19 outcomes, which found Black patients had a higher hospitalization rate, 8 increased odds of positive test results, 12…”
Section: Discussionsupporting
confidence: 90%
“…health conditions, such as obesity, cancer, type 2 diabetes, and renal conditions, were prevalent among patients with worse COVID-19 outcomes. 34,45,46,55 Notably, our findings largely agree with recent published work examining racial/ethnic differences in COVID-19 outcomes, which found Black patients had a higher hospitalization rate, 8 increased odds of positive test results, 12…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, a mortality rate of 19.5% (38,812/198,879) had been reported in patients with pre-existing illness whereas only 1.6% (1,431/88,441) of COVID-19 patients with no preexisting health illness have died 19 . Similar higher mortality rate of 42.5% (7558/36398) among the COVID-19 patients with pre-existing illness has also been reported by Khan and his colleagues in their systematic review on COVID-19 patients 20 . These results vividly illustrate that the patients are dying due to pre-existing conditions rather than COVID-19.…”
Section: Introductionsupporting
confidence: 81%
“… 5 , 6 This was reciprocated in a systematic review of n = 12 760 individuals by Khan et al., which found 1.4% (n = 355) of their COVID-19 positive cohort had asthma as a comorbidity. 7 Other studies worldwide have demonstrated an increased prevalence of asthma in COVID-positive individuals and have suggested that the lower prevalence of asthma reported within some studies could be attributed to underreporting, underdiagnosis or poor recognition of chronic respiratory disease in patients with COVID-19 infection. 8 Additionally, another explanation for the differing rates of comorbid asthma seen among studies may be due to the overall differences in rates of comorbidities including asthma in different countries.…”
Section: Does Asthma Increase the Risk Of Covid-19 Infection (See mentioning
confidence: 97%